2020
DOI: 10.1007/s00784-020-03267-8
|View full text |Cite
|
Sign up to set email alerts
|

Health services provision of 48 public tertiary dental hospitals during the COVID-19 epidemic in China

Abstract: Objectives To assess the status of health services provision of public tertiary dental hospitals during the COVID-19 epidemic in China and to evaluate the regional difference of telehealth. Materials and methods The health services provision of public tertiary dental hospitals in China mainland during the COVID-19 epidemic was inquired. The status of non-emergency dental services, emergency dental services, and online professional consultation and the hospitals' geographical distribution were recorded and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
127
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 7 publications
2
127
1
8
Order By: Relevance
“…delivered teleradiology services and provided teleconsultation for triage of COVID-19 infection through a social media massager (33). In addition to taking actions to protect the health and safety of patients, staff should also take mobile health technology to develop sta ng plans and conduct billing for healthcare services (39).…”
Section: Discussionmentioning
confidence: 99%
“…delivered teleradiology services and provided teleconsultation for triage of COVID-19 infection through a social media massager (33). In addition to taking actions to protect the health and safety of patients, staff should also take mobile health technology to develop sta ng plans and conduct billing for healthcare services (39).…”
Section: Discussionmentioning
confidence: 99%
“…During the SARS-COV-2,the number of emergency dental patients increased by 29.73% compared with the pre SARS-COV-2 and the average daily visits increased by 14.8.This is mainly due to the high risk of dental treatment under the in uence of the SARS-COV-2,which leads to the decrease or closure of the general outpatient clinics of stomatological hospitals or clinics in China and the failure of regular examination and treatment of patients in a timely manner,which leads to the aggravation of the condition and aggravation of the pain,thus increasing the demand for dental emergency services,leading to the increase in the number of emergency visits [7,15].Regarding the weekly variation of the number of days visited,the number of patients visited on the weekend in the previous epidemic period was higher than the number of patients visited on the week,which was consistent with the distribution of dental emergency time in South Korea [16].With the outbreak,this difference becomes less pronounced and the distribution of daily and weekly visits after the outbreak decreases,which may be related to the increased demand for emergency dental services.In terms of visiting time,the pre-epidemic group in this study and another study on emergency visits in South Korea [16,17] showed a similar distribution of visiting time in dental emergency patients,both of whom had a peak visiting time at night.During the epidemic,the number of patients visiting during the daytime increased except for the night peak [2,18],which was related to the decrease of dental outpatient service during the SARS-COV-2 and patient's demand for medical treatment through emergency treatment.Therefore,dental emergency centers in a region should increase personnel and material support for dental emergency centers in the face of respiratory infectious disease emergencies, so as to cope with the increased emergency needs of dental emergency patients due to the closure of clinics [19].…”
Section: Discussionmentioning
confidence: 99%
“…The composition and characteristics of emergency dental care are in uenced by environmental changes,lifestyle,economic and sociocultural in uences [6].With the spread of SARS-COV-2 around the world,people adopt home isolation to reduce going out and gathering,resulting in changes in the living environment,psychological status and lifestyle of the population [7].The composition of dental emergency diseases also presents different changes and characteristics.Most of the risk factors associated with dental emergencies are considered to be preventable [6,8].Characteristics of dental emergency patients under the in uence of SARS-COV-2 have been reported,There is a lack of comparison with the situation before the SARS-COV-2 [9].To analyze the incompleteness of the types of emergency diseases [1,9]. Hospitals and clinics choose to reduce or stop visits in order to ensure the safety of doctors and patients under the impact of the SARS-COV-2,At the same time,the dental treatment process has also changed accordingly [1,9,10],dental protection needs to be strengthened during treatment,reduced use of some dental appliances that cause spatter,changes in treatment choices and drug use all in uence the effective operation of dental emergencies [10,11].So master dental emergency diseases distribution and the change law of demographic characteristics for dental emergency center in the face of strong public health emergencies of infectious respiratory disease,can not only improve the e ciency of treatment of dental emergency patients,at the same time can provide dental emergency personnel,supplies, and emergency technical expertise to provide important reference data [12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid spread of COVID‐19, the risk of it causing significant fatality and the stress it poses for health care workers and its potential to overwhelm the capacity of health care systems resulted in many countries adopting measures to restrict human mobility, in an attempt to limit the spread of the disease 11,12 . Included in these restrictive measures are oral health care providers who were required to halt all nonemergency oral health care procedures, as many dental procedures produce aerosols and COVID‐19 spreads mainly by aerosols 13‐15 . Another issue was to limit the use of personal protective equipment (PPEs) by dentists, as they were required for hospitals and were in short supply globally 13,16 …”
mentioning
confidence: 99%